Os huumari, o obi e o hyri: a circulação dos entes no cosmo Karajá - Andrade, Rafael Santana Gonçalves de (2016)
This work started from the analysis of the Karajá collection of the American anthropologist William Lipkind, kept in the Museu Nacional collection (UFRJ – Brazil). The analysis was focused on the shaman‟s things, as the obi, the hitxiwa and the rata(k)ana, which were presented through photographic cards to some Karajá interlocutors in the village of Santa Isabel do Morro (TO). From a brief ethnographic experience, it was possible to reach the ideas presented here. These shaman's things pointed to the specificity of the movement of “being” in the Karajá cosmos, configuring the nonindigenous “world” as one of the possible places in this cosmos where these things circulate. In the system of meanings shared by the karajá, the concept of object, lifeless and inert, is far from the subjectivity and life present in the relationships surrounding things. This Karajá approach leads us to rethink the status of collection items and the way they were and are collected, at the same time that they raise some questions about the need and the significance to store and expose such things in museums.